Islamization of Science from a Historical-Philosophical Perspective - Mochammad Achwan Baharuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2022)
This paper discusses the idea of science which tends to get a negative response and does not develop. In fact, the main goal is to provide a new awareness in obtaining modern knowledge in accordance with the needs of Muslims. The main focus of writing is how the nature or purpose of the Islamization of Science. The main focus is discussed with a descriptive qualitative method through a historical-philosophical approach based on literature data. This paper shows that the essence of the idea of the Islamization of science is a movement for the renewal of science which bases itself on the fact that modern science is developing contrary to religion, so there is a need for a cleansing liberation movement. This idea has major implications, namely right and wrong between science and religion. In fact, the standard of truth is different from one another so that it forces the truth of one (religion) to justify knowledge or vice versa creates an attitude of human disharmony. Therefore, there is a need for a new awareness that respects the differences between the two in obtaining new knowledge in order to build a more advanced human civilization.